Women Political Participation in the Era of Prophet Muhammad: Study on the Hadith Transmitters of the Women Companions - Zunly Nadia (Al-Albab, 2017)
Most of Moslem societies define the role of woman in the purely domestic sector. Some people consider that Islam stands against women’s role in public sectors believing that it has roots in the context of the prophet’s time. This work shows that there is no prohibitation for woman to take parts in the public and social affairs including in the area of political role. It was the case that some women companions of the prophet participated in the political role including Aisyah the wife of Nabi Saw, Asma binti Abu Bakar, Ummu Athiyah, Ummu Hani’ and Rubayyi’ bint Mu’awidz. In this paper, the writer focuses on woman companion hadith transmitters who are directly wrapped up in the missionary work with the prophet. In addition, this paper also shows the relation between woman companion transmitter activities and their hadith transmission, under assumption that the role of woman would influence the texts of the transmitted hadiths. It is because, as a text, hadith was transmitted in the certain context and condition. Accordingly, every transmitter had different hadith transmission based on her context, status, profession, and even gender construction. Therefore, this paper discusses the woman companion transmitters who play their role in the field of politics and also their influence in their transmitted hadiths